Upaya Guru Pendidikan Agama Islam Dalam Pembinaan Etika Komunikasi Siswa - Hasan, sholeh; Indriyani, Tia; Amin, Saiful (JUPIN (Jurnal Pendidikan Islam Nusantara), 2023)
This exploration was roused by the way that analysts observed that there were still understudies at SMA Negri 1 Belitang Jaya who needed great and respectful correspondence morals. Understudies fail to see how to impart well. There are understudies who say brutal words toward the start of educating and learning exercises, talk or contend during class when the instructor is making sense of something, play hooky, or even need to smoke during class. In light of these issues, analysts are keen on assuming control over the examination area of SMA Negeri 1 Belitang Jaya. The detailing of the issue in this exploration is what endeavors do PAI educators make to further develop correspondence morals among understudies at SMA Negeri 1 Belitangg Jaya? The point is to see if the Islamic Strict Instruction Educator at Belitang Jaya Secondary School puts forth these attempts or not. This exploration philosophy is subjective and elucidating approach. Islamic strict schooling educators and understudies participated in this exploration. Essential and auxiliary sources were utilized to gather information. Perceptions and narratives are instances of essential sources, while diaries and logical articles are instances of auxiliary sources. Information examination utilizes interpretive examination, in particular utilizing the specialist's creative mind, instinct and imaginative capacities in a cycle called reflection to catch the significance of occasions connected with the exploration subject. The reason for this examination is to recognize and figure out the significance of the exploration subject. The consequences of the exploration show that Islamic strict educators attempt to show correspondence morals to understudies at SMA Negeri 1 Belitang Jaya. executes it utilizing three methodologies, in particular: To begin with, through giving inspiration, where the instructor attempts to stimulate, increment and keep up with the energy of understudies so they work on themselves and have great correspondence morals. Second, by giving direction, to be specific through headings and models given by educators to youngsters, empowering them to be considerate, regard guardians, educators and companions while connecting in the school and local area climate. Third, through adjustment, by shaking hands and making proper acquaintance while meeting an instructor or companion, as well as perusing petitions when learning. The point is for understudies to be prepared and familiar with continuously showing acceptable conduct and perspectives, since adjustment is a vital premise in the improvement of understudy correspondence morals.